Comparison of Early Childhood Vocabulary Development in Digital and Conventional Learning - Halmina, Andi; Palupi, Tri Nathalia (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
Vocabulary development is a fundamental component of early childhood language acquisition and plays a crucial role in children’s cognitive growth and future academic success. The rapid integration of digital technology into early childhood education has raised questions regarding its effectiveness compared to conventional learning approaches in supporting vocabulary development. This study aims to compare early childhood vocabulary development in digital learning and conventional learning contexts. The research employed a qualitative approach using a literature study design. Data were collected from reputable national and international journals, books, and research reports related to early childhood vocabulary development, digital learning, and conventional learning. The selected literature was analyzed using content analysis to identify patterns, similarities, and differences between the two learning approaches. The findings indicate that digital learning effectively supports receptive vocabulary development and initial word recognition through multimodal features such as visuals, audio, and interactivity, particularly when accompanied by adult guidance. In contrast, conventional learning demonstrates stronger outcomes in expressive vocabulary development, pragmatic language use, and deeper semantic understanding through face-to-face interaction, dialogic reading, and guided communication. Overall, the study concludes that digital and conventional learning offer complementary benefits, and a blended learning approach provides the most effective support for early childhood vocabulary development.